1989
DOI: 10.1111/j.1365-2133.1989.tb01346.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin gene-related peptide immunoreactivity in prurigo nodularis: a comparative study with neurodermatitis circumscripta

Abstract: Eight patients with intensely pruritic lesions of chronic idiopathic prurigo nodularis and three patients with neurodermatitis circumscripta were investigated using the indirect immunofluorescence method. Results showed similarities in epidermal hyperplasia but not in nerve proliferation and neuropeptide immunoreactivity. Increased numbers of calcitonin gene-related peptide (CGRP) and substance P immunoreactive nerve fibre bundles were detected in specimens taken from prurigo nodularis lesions, but no increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 12 publications
0
27
1
Order By: Relevance
“…Next, to evaluate the effects of skin-scratching on cutaneous hypersensitive responses and/or on susceptibility to neurogenic inflammation, we examined SP-or CGRP-immunoreactivity on cutaneous nerve fibers after a single skin-scratching. SP-or CGRPimmunoreactive nerve fibers increase in patients with pruritic skin diseases such as atopic dermatitis and nodular prurigo [5,[20][21][22][23]. Our findings revealed that significant increases in SP-or CGRP-immunoreactive nerve fibers developed at about day 7, when the number of PGP9.5-immunoreactive nerve fibers was at its peak.…”
Section: Discussionmentioning
confidence: 54%
“…Next, to evaluate the effects of skin-scratching on cutaneous hypersensitive responses and/or on susceptibility to neurogenic inflammation, we examined SP-or CGRP-immunoreactivity on cutaneous nerve fibers after a single skin-scratching. SP-or CGRPimmunoreactive nerve fibers increase in patients with pruritic skin diseases such as atopic dermatitis and nodular prurigo [5,[20][21][22][23]. Our findings revealed that significant increases in SP-or CGRP-immunoreactive nerve fibers developed at about day 7, when the number of PGP9.5-immunoreactive nerve fibers was at its peak.…”
Section: Discussionmentioning
confidence: 54%
“…17 However, Vaalasti et al . 18 observing indirect immunofluorescence, noted that nervous bundles obtained from PN lesions showed increased immunoreactivity to substance P and calcitonin gene‐related protein (CGRP). These findings were not observed in specimens obtained from patients with circumscribed neurodermatitis compared with normal skin.…”
Section: Aetiology Pathogenesis and Morbid Associationsmentioning
confidence: 99%
“…It is also known that intradermal injection of SP or VIP provokes itching in healthy subjects (16,17). In addition, increased expression of several neuropeptides was detected in other pruritic dermatoses, such as atopic eczema and prurigo nodularis (17)(18)(19). To prove whether neuropeptides are involved in the pathogenesis of pruritus in psoriasis we correlated the plasma levels of SP, CGRP, VIP and NPY with the presence of pruritus and its intensity in patients with psoriasis.…”
mentioning
confidence: 97%